TANTANGAN GURU SEKOLAH DASAR DALAM PRAKTIK PEMBELAJARAN ABAD 21 PADA UNSUR KETERAMPILAN BERPIKIR KRITIS SISWA DIKELAS II SD N 2 KARANGANYAR PURBALINGGA - Nur, Nur Wulan Safitri; Ana Andriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The implementation of critical thinking skills in the basic education curriculum in the 21st century presents real challenges for educators, especially in the realm of primary level education. This study examines in depth the challenges faced by second grade teachers at SD Negeri 2 Karanganyar Purbalingga. Application of critical thinking skills elements in the learning stages. This research applies a qualitative case study approach, where data is collected through observation, interviews, and documentation analysis. The findings of the research show that teachers experience various challenges in their learning practices, including one of the limitations in understanding the concept of critical thinking; the lack of professional training that is aligned with the principles of 21st-century learning has not been fully met; and the limited availability of adequate media and learning resources contributes to the challenges in efforts to stimulate students' critical thinking skills. Internal learner factors, such as low curiosity and language limitations, act as barriers to the development of critical thinking skills from an early age. In classroom management, teachers are faced with challenges in order to achieve optimal learning outcomes and in line with the main considerations with the cognitive stages of students II so that teachers can design more meaningful learning experiences. This research shows that improving teachers' competencies through continuous training and the provision of relevant learning resources play an important role in supporting the success of 21st century skills-based learning. The findings of this study are expected to have essential contributive potential and seek to enrich understanding among academics, educational practitioners and policy makers regarding improving the quality of learning in the early phases of formal education.